Online Brand Communities Using the Social Web for Branding and Marketing - Martínez-López, Francisco J.; Anaya, Rafael; Aguilar, Rocio; Molinillo, Sebastián (Progress in IS, 2016)
This book presents and analyzes the concept of online brand communities, an emerging and exciting topic in marketing and eCommerce. First, it lays out the foundations like the evolution of the Web and the so-called Social Web, its utility for users and businesses, and the evolution of the marketing mind-set to adapt the Social Web. On this basis, the book then presents a detailed analysis of online brand communities, examining the concept of virtual community with a specific focus on virtual brand communities. In this context the book also explores recent trends related to branding and brand management. Next, it proposes a classification system for online brand communities, taking into account questions like the motivating factors for consumers to join, participate and stay in a community. The process of value creation in communities is examined from both business and consumer perspectives. The book draws to a close with a brief presentation of the process broadly accepted for the successful development of online brand communities. .